QUALITY AND LIBRARY EDUCATION: A PHENOMENOLOGICAL STUDY OF LIS FACULTY CONCEPTUALIZATIONS OF LIBRARY PROGRAM CURRICULUM - Baker, Elizabeth (East Carolina University, 2019)
This dissertation aimed to examine the perceptions of faculty about the curriculum taught in a Master’s level degree library program. It was motivated by one research question: How do faculty in a Library and Information Studies (LIS) program in the United States conceptualize a quality library education? It utilized a two-part conceptual framework, particularly relying on the work of Harvey and colleagues (Harvey, 2001; Harvey & Green, 1993; Harvey & Newton, 2004; Stensaker & Harvey, 2010) in which they conceptualized quality in higher education as exceptionalism, perfectionism, fitness-for purpose, value-for-money, transformation, compliance, political or symbolic, employability, and accountability and Argyris and Schon (1992) in which theories-in-use are the actual beliefs and practices while espoused theories are the professed beliefs and practices of professionals. This study employed a phenomenological methodology, utilizing the lifeworld approach as conceptualized by Dahlberg, Dahlberg, and Nystrom (2008), which stresses a whole-part-whole approach to data analysis. The study concluded that the faculty in the selected LIS program conceptualize a quality library education for their students as community building, student engagement, service, student learning, employability, and transformation. Thus, the faculty in this study identified only two of the nine elements of a quality education as conceptualized by Harvey and colleagues (Harvey, 2001; Harvey & Green, 1993; Harvey & Newton, 2004; Stensaker & Harvey, 2010). Using the study’s findings as their theories-in-use and the program’s learning outcomes as their espoused theories, it was determined that these two elements mostly match each other, with the exception of student engagement not explicitly appearing in their espoused theories.
Keywords: quality; LIS faculty; LIS education; LIS faculty perceptions; theories-in-use; phenomenology; Lifeworld approach; Library education--United States; Academic achievement; Education, Higher--Aims and objectives--United States